Strategi Pemasaran Produk Gadai Emas dalam Menarik Nasabah Pada PT. Bank Riau Kepri Syariah Capem Duri - Fitri, Mariatul; Makruflis, Makruflis; Irma Ningsih, Hesty (Fakultas Ekonomi dan Bisnis Islam, 2023)
This study aims to analyze the marketing strategy of gold pawn products in an effort to attract customers at PT. Bank Riau Kepri Syariah Capem Duri. Gold pawn is one of the sharia banking products that offers financial solutions with gold collateral, which attracts public interest. The research method used is qualitative descriptive with a case study approach. Data were obtained through interviews, observations, and documentation from various related sources. The results of the study indicate that effective marketing strategies include intensive advertising campaigns, the use of social media for promotion, and education and counseling to the public about the benefits of gold pawn. Bank Riau Kepri Sariah (BRKS) is a Sharia Macro Financial Institution (LKMS); A large financial institution with a business model based on Islamic Sharia. Bank Riau Kepri Syariah focuses on offering its products, one of which is the Gold Pawn (RAHN) product. From the graph above, it can be seen that the number of customers per year is low and tends to decrease. Then deposit the gold (rahn) at the Bank Riau Kepari Syariah Duri branch according to the method of sale. 4 of the 7 elements of the marketing mix (product, price, place, promotion, people, physical evidence and process) are focus elements or known as the 4Ps (price, place, promotion and strategy).